Dietary Inflammatory Index and Risk of Asthenozoospermia: A Hospital-Based Case-Controlled Study in China - Liu, Fang-Hua; Wang, Xiao-Bin; Wen, Zhao-Yan; Wang, Han-Yuan; Zhang, Meng; Zhang, Shuang; Jiang, Yu-Ting; Zhang, Jia-Yu; Sun, Hui; Pan, Bo-Chen; Wu, Qi-Jun (Frontiers in Nutrition, 2021)
Background Evidence of associations between a pro-inflammatory diet and asthenozoospermia risk is limited. We therefore performed a case-controlled study to investigate associations between pro-inflammatory diet using dietary inflammatory index (DII) scores and asthenozoospermia risk in China. Methods Our hospital-based case-controlled study comprised 549 incident asthenozoospermia men and 581 healthy controls. All were interviewed at the infertility clinic in Shengjing Hospital of China Medical University from June 2020 to December 2020. DII scores were calculated based on dietary intake which were assessed using a validated food frequency questionnaire. Semen parameters were analyzed according to World Health Organization guidelines. An unconditional logistic regression model was used to estimate odds ratios (ORs) and corresponding 95% confidence intervals (CIs) for asthenozoospermia risk. The lowest tertile served as the reference category for regression analyses. Results After adjustment for age in the primary multivariable model, we failed to determine a significant negative association between DII and asthenozoospermia risk (for the highest tertile of DII scores compared to the lowest tertile) (OR = 0.77, 95% CI: 0.57-1.03). Similarly, non-significant associations were also identified in the multivariable model after adjusting for more potential confounders (OR = 0.86; 95% CI: 0.58-1.27). Additionally, in subgroup analyses stratified by age, body mass index, and smoking status, non-significant results were consistent with the main findings. Conclusions To our knowledge, this is the first study exploring this particular topic. Our research does not support an association between DII scores and asthenozoospermia risk. Further prospective studies with more DII relevant foods and nutrients are warranted to confirm our findings.